Legal Protection Copyright of Non-Fungible Token-Based Painting Works (NFT) in Indonesia - Yustisio, Rifki; Asshidiq, Abdullah Widy; Wafi, Muhammad Syafiq (PUSKAPSI Law Review, 2023)
In the midst of increasingly massive digitalization and modernization, the use of technology and information in producing masterpieces has brought new problems, one of which is related to digital-based copyright protection. In the background of this, this research then produces 2 (two) problem formulations that need to be researched, namely: how is the protection of copyright of Non-Fungible Token (NFT) based paintings in Indonesia? And what are the obstacles in the protection of copyright of Non-Fungible Token (NFT) based paintings in Indonesia?. This research is empirical research, with a sociological approach research method. The results showed that, Non-Fungible Token (NFT) as a digital work of art, civilly categorized as "rights" according to article 499 of the Civil Code, by Law Number 28 of 2014 concerning Copyright, is still recognized as one of the protected objects. More than that, the obstacles found by researchers related to copyright protection of digital-based paintings, based on the results of interviews at the Ministry of Law and Human Rights of the Special Region of Yogyakarta and the Special Criminal Investigation Directorate of the Yogyakarta Police, among others: Regulatory Factors, Law Enforcement Factors, Supporting Facilities and Facilities, Individual, Environmental and Community Factors. Keywords: Non-Fungible Token, copyright protection, technology